Nacionalizar al indio, etnizar la nación: América Latina frente al multiculturalismo - Gros, Christian (Sociedad y Economía, 2005)
This paper goes through the situation of Latín American countries that at the end of the Twentieth Century modified their constitutions in order to build in the recognition of the ethnic and cultural diversity of the their Indian peoples. This process entails an essential transformation of the meaning of nationality in regard to what has been the conformation of a sense of nation along many decades of history in these countries. The author points to the fundamental role of the State, to the reasons that allowed the emergence of mis transformation, and to the consequences they have upon the current and future condition of the indigenous populations